Measuring health-related quality of life in elementary and secondary school students using the Chinese version of the EQ-5D-Y in rural China - Chen-Wei Pan; Hua Zhong; Jun Li; Chen Suo; Pei Wang (BMC, 2020)
Abstract Background To measure health-related quality of life (HRQOL) of elementary and secondary school students in rural China using the simplified Chinese version of the EQ-5D-Y. Method Both the samples of students were from a school-based cohort study in a county located in southwestern China. The students self-completed the EQ-5D-Y. Feasibility was evaluated according to the percentages of missing values. Known group validity was assessed by comparing the frequency of reporting EQ-5D-Y problems between groups known to differ in health status. Results A total of 1728 elementary students and 2116 secondary students were included in the analysis. Their respective mean age was 8.7 (range: 7-15) years and 14.8 (range: 11-18) years, with girls being 45.1 and 50.1%, respectively. The missing values in both samples were quite low. Elementary students were less likely to have problems on'having pain or discomfort' and 'feeling worried, sad or unhappy' dimensions, but more likely to report problems on the dimensions related to physical functioning. Gender difference in HRQOL was only detected for secondary students in terms of 'doing usual activities', 'having pain or discomfort,' and 'feeling worried, sad or unhappy' (P < 0.05 for all). The significant differences in HRQOL were not observed for the other characteristics. Conclusions It appears that the EQ-5D-Y is feasible and valid instrument in school-aged children and adolescents in rural China; but it suffers from similar disadvantages to those found in other general populations. The HRQOL distributions measured by the EQ-5D-Y were also provided.